Chemical characterisation, insecticidal and antioxidant activities of essential oils from four Citrus spp. fruit peel waste. (December 2022) - Visakh, Naduvilthara U.; Pathrose, Berin; Chellappan, Mani; Ranjith, M.T.; Sindhu, P.V.; Mathew, Deepu
Abstract: Citrus peel is a major fruit waste generated during the processing of citrus fruits. We extracted and chemically characterised essential oil from four different species of citrus peel waste and evaluated its insecticidal, antioxidant and phytotoxic activities. GC-MS/MS characterisation revealed D-limonene as the major constituent of citrus peel waste essential oil. The essential oils from the four citrus peel wastes showed significant contact, fumigant and repellent activities against two key stored grain pests Tribolium castaneum (Herbst) and Callosobruchus chinensis (L.). DPPH, ABTS, and FRAP assays revealed the antioxidant potential of the citrus peel waste essential oil. The essential oil did not affect the germination of wheat seeds and revealed the safety of essential oil to germinating seeds. Hence, the essential oil extracted from citrus peel waste can be valorised and utilised as a botanical insecticide against T. castaneum and C. chinensis . Graphical abstract: Image 1 Highlights: Chemically characterised four different species of citrus fruit peel waste. The predominant phytochemical constituent in citrus peel was D-limonene. Citrus aurantifolia exhibited the best insecticidal activities. The antioxidant potential of citrus peel waste was determined. Citrus peel waste essential oils can be considered a source of phytochemicals with insecticidal and antioxidant properties.